Juzefo Jasinskio asmeninė biblioteka - Balčienė, Irena (Knygotyra, 1998)
We have some knowledge of the first private libraries in Lithuania from the end of XIV century.The present article deals with the private book collection of Joseph Jasinski (?-1560), archdeacon of Vilnius, nobleman, mecenas etc. He had a big collection of rare books and donated it to his nephew Nicolaus Jasinski (?-1600), canon of Vilnius. N. Jasinski increased the private collection and donated it to the Vilnius Bernardines cloister. After the Russian government closed the cloister (in 1864) the library was dispersed. The majority of these books were transferred to Vilnius University Library. There are seven books of Joseph Jasinski in Vilnius University Library: 2 incunabula, 4 paleotypes and one book printed in 1551. They are described in the article with special focus on proveniences, binding evidence, contents of books.One of J. Jasinski books now is held in the Library of Academy of Sciences in Saint Petersburg. The First Statute of Lithuania (Kodeks Olszewski) handwritten copy from 1550 was also in the private collection of J. Jasinski. Now this manuscript book is held in the National Library of Poland (Warsaw). It is possible that some other books of J. Jasinski would be found in libraries of Lithuania, Poland or Russia.The present article is the first attempt to draw attention to J. Jasinski's private book collection.